Long distance disparity processing in the human visual cortex: an EEG source imaging study - Cottereau, B.; Norcia, A.; Tsai, T.-H.; Mckee, S. (Journal of vision (Charlottesville, Va.), 2010)
We estimated the relative disparity response of neural populations in different visual areas in human cortex with visual evoked potentials and source localization methods. Using dense dynamic random dot patterns, we modulated the disparity of a central disk (4 degree diameter) from 0 to 12.6' uncrossed disparity at 2 Hz. The disk was surrounded by a static annulus (16 degree outside diameter) presented in the fixation plane. We varied the gap separating the disk from the annulus parametrically from 0 to 5.5 degrees in six separate conditions. We compared the response amplitudes as a function of gap size to responses to the disk alone within fMRI-defined ROI's across the visual cortex. Based on the average signal-to-noise ratio (6 subjects) for the first harmonic (2Hz), we found that there was no change in response amplitude for small separations (<0.5 deg) in all visual areas. At larger separations, the amplitudes in V2 and V3 ROIs decreased to levels comparable to those obtained in the absence of a surround. However, in the V3A ROI, the amplitude remained constant until the gap size exceeded 4 degree and then fell to the level observed for the no-surround condition. To determine whether this effect was due to the decreasing size of the annular surround, we performed a control experiment, using two annuli of vastly different areas, but separated from the disk by the same gap width (0.5 deg); the responses were identical for these two surrounds. Altogether, these results suggest that area V3A possesses neurons responsive to relative disparity whose receptive fields allow a robust estimation of relative depth even for disparities separated by up to 4 degrees.